Avoidance of soccer injuries with preseason conditioning - Heidt, R. S.; Sweeterman, L. M.; Carlonas, R. L.; Traub, J. A.; Tekulve, F. X. (The American Journal of Sports Medicine, 2000)
The effect of a preseason conditioning program was studied to evaluate its influence on the occurrence and severity of soccer injuries. Three hundred female soccer players (ages 14 to 18 years) were studied over a 1-year period. Forty-two of these players participated in a 7-week training program before the start of the season. The type, mechanism, and severity of the injury, when the injury occurred, the number of games or practices missed, and type of shoe worn were recorded. All injuries occurred in the lower extremities, with 61.2% occurring at the knee and ankle. Student's t-test evaluations revealed that the trained group experienced a significantly lower incidence of injury than the untrained group (P = 0.0085). Although not statistically significant, the trained group also had a lower percentage (2.4%) of anterior cruciate ligament injuries compared with the untrained group (3.1%). These results suggest that this type of conditioning has a significant influence on lowering the incidence of injury in female adolescent soccer players.